THE CRIMINAL LIABILITY OF ARTIFICIAL INTELLIGENCE: IS IT PLAUSIBLE TO HITHERTO INDONESIAN CRIMINAL SYSTEM? - Rofi Aulia Rahman; Rizki Habibulah (Faculty of Law, University of Muhammadiyah Malang, 2019)
The pace of technology evolution is very fast. The technology has brought us to the limitless world and becoming our ally in every daily life. The technology has created a visionary autonomous agent that could surpass human capability with little or without human intervention, called by Artificial Intelligence (AI). In the implementation of AI in every area that could be in industrial, health, agriculture, artist, etc. Consequently, AI can damage individual or congregation life that is protected by criminal law. In the current Indonesian criminal system, it just acknowledges natural person and legal person (recht persoon) as the subject of law that can be imposed by criminal sanction. Hitherto and near foreseeable future AI has a notable role in every aspect, which affects also criminal aspects due to the damage resulted. AI has no sufficient legal status to be explained in the Indonesian criminal system. In this paper, the author will assess whether the current criminal system of Indonesia can sue the criminal liability of artificial intelligence, and also will make it clear to whom the possibility of criminal liability of artificial intelligence shall be charged.